Low-loss inductance magnetic core and preparation method thereof

By using an insulating coated adhesive with an addition-shaped curable silicone resin and a low-melting glass powder, the problem of air gaps during high-temperature sintering is solved, and the magnetic performance and density of the low-loss inductive core is significantly improved.

CN119480413AActive Publication Date: 2025-02-18QINGYUAN ZHENDONG ELECTRONIC TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411671038.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The organic resins and organic lubricants used in the high-temperature sintering process in the prior art will generate excessive air gaps, resulting in a decrease in the magnetic core permeability and an increase in the hysteresis loss, and reduce the overall magnetic performance.

Method used

Additive curable silicone resin is used as the adhesive for ferrite magnetic powder, and low-melting point glass powder is added to the insulating coated adhesive, and low-loss inductive magnetic core is prepared by molding and curing molding and sintering.

Benefits of technology

It significantly improves the insulation coating effect and core density, reduces losses, and improves magnetic performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic materials, and particularly relates to a low-loss inductance core and a preparation method thereof. The preparation method comprises the following preparation steps: (1) uniformly mixing vinyl silicone oil, hydrogen-containing silicone oil, a platinum complex catalyst, an inhibitor and low-melting-point glass powder at normal temperature to obtain an insulating coating adhesive; and (2) uniformly mixing the obtained insulating coating adhesive with ferrite magnetic powder, carrying out mold pressing curing molding at the temperature of 60-100 DEG C and under the pressure of 200-500 MPa, and then heating to 500-800 DEG C for sintering treatment to obtain the low-loss inductance magnetic core. The addition type curable organic silicon resin is adopted for bonding the ferrite magnetic powder, curing forming can be conducted under the lower pressure, the filling effect of the high-temperature sintering low-melting-point glass is combined, the insulation coating effect and the density of the magnetic core obtained after mold pressing curing forming can be remarkably improved, and therefore loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a low-loss inductor magnetic core and a preparation method thereof. Background Art

[0002] According to its composition, the inductor core mainly includes ferrite core, iron alloy core and amorphous nanocrystalline soft magnetic alloy core. It is a soft magnetic material made of magnetic powder after insulation coating and pressing and sintering. It is widely used in life due to its excellent magnetic properties, such as wireless communication sensors, transformers, automobiles and other fields. However, with the development of modern society, people's requirements for high-frequency applications of electronic devices have been further improved, and low-loss soft magnetic composite materials have become a hot research topic.

[0003] Patent CN 114360884 A discloses a method for preparing a high magnetic induction and low loss gradient nanocrystalline magnetic powder core, wherein Fe-based amorphous alloy powder is treated by discharge plasma to nanocrystallize the surface layer of the amorphous powder, and then pressed and formed by adding a coating agent and a lubricant, and finally sintered at a temperature higher than the crystallization temperature of the Fe-based amorphous alloy powder, so that the nanocrystals on the surface of the powder continue to grow and the amorphous inside the powder is nanocrystallized to form a gradient difference in grain size, thereby obtaining a high magnetic induction and low loss gradient nanocrystalline magnetic powder core with large grains on the outer layer and small grains on the inner layer. Patent CN 116598117 A discloses a method for preparing a high magnetic induction and low loss amorphous / nanocrystalline magnetic powder core based on a magnetically conductive insulating shell core-shell functional unit, wherein an insulating shell that is both insulating and magnetically conductive is coated on the surface of a micron iron-based amorphous / nanocrystalline powder core to form a magnetically conductive insulating shell functional unit, and then a high magnetic induction and low loss composite magnetic powder core is obtained by combining pressing and sintering processes. Although the above-mentioned prior art can achieve good insulation coating effect to reduce eddy current loss, the organic resin and organic lubricant used in the insulation coating will produce excessive air gap during the high-temperature sintering process, resulting in a decrease in the magnetic permeability of the magnetic core and an increase in hysteresis loss, thereby reducing the overall magnetic performance. Summary of the invention

[0004] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing a low-loss inductor core.

[0005] Another object of the present invention is to provide a low-loss inductor core prepared by the above method.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0008] (1) Preparation of insulation coating adhesive:

[0009] The vinyl silicone oil, hydrogen-containing silicone oil, platinum complex catalyst, inhibitor and low-melting-point glass powder are uniformly mixed at room temperature to obtain an insulating coating adhesive;

[0010] (2) Preparation of low-loss inductor core:

[0011] The obtained insulating coating adhesive is mixed evenly with ferrite magnetic powder, firstly molded and cured at a temperature of 60-100°C and a pressure of 200-500MPa, and then heated to 500-800°C for sintering to obtain a low-loss inductor magnetic core.

[0012] Furthermore, the vinyl silicone oil in step (1) has a viscosity of 100 to 2000 mPa·s and a vinyl content of 1% to 10%.

[0013] Furthermore, the hydrogen-containing silicone oil in step (1) has a viscosity of 100 to 2000 mPa·s and a hydrogen content of 0.2% to 1.5%.

[0014] Further preferably, the mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 1:0.1-0.6.

[0015] Furthermore, the amount of the platinum complex catalyst added in step (1) is 0.005% to 0.02% of the total mass of the vinyl silicone oil and the hydrogen-containing silicone oil.

[0016] Furthermore, the inhibitor in step (1) is an acetylene alcohol inhibitor, and the amount of the acetylene alcohol inhibitor added is 0.05% to 0.2% of the total mass of the vinyl silicone oil and the hydrogen-containing silicone oil.

[0017] Furthermore, the low-melting-point glass powder in step (1) has a particle size of 1 to 10 μm and a melting point of 300 to 600° C.

[0018] Further preferably, the added amount of the low melting point glass powder is 5% to 40% of the total mass of the vinyl silicone oil and the hydrogen-containing silicone oil.

[0019] The relative amount of low-melting-point glass powder added in the present invention has a significant impact on the strength and loss of the obtained inductor core. When the amount of low-melting-point glass powder added is too low, the air gap generated by the high-temperature sintering of the insulating coating adhesive cannot be effectively filled, resulting in an increase in hysteresis loss; when the amount of low-melting-point glass powder added is too high, the bonding and curing performance of the insulating coating adhesive is reduced, resulting in a reduction in the insulating coating effect and a reduction in the density of the magnetic core after molding and curing, which also leads to an increase in eddy current loss and hysteresis loss.

[0020] Furthermore, the ferrite powder in step (2) is manganese-zinc ferrite powder or nickel-zinc ferrite powder with a particle size of 1 to 10 μm.

[0021] Furthermore, in step (2), the mass ratio of the insulating coating adhesive to the ferrite magnetic powder is 1:10-100.

[0022] Furthermore, the pressure-maintaining sintering treatment in step (2) is carried out under air conditions, and the time of the pressure-maintaining sintering treatment is 15 to 60 minutes.

[0023] A low-loss inductor magnetic core is prepared by the method.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention adopts addition-curable silicone resin as the adhesive of ferrite magnetic powder. Compared with conventional organic resin adhesives such as epoxy resin adhesives, the present invention has lower curing shrinkage and better toughness. At the same time, the porous SiO2 generated by the silicone resin adhesive during the later high-temperature sintering process can be used as a filling carrier for low-melting-point glass, which can significantly improve the insulation coating effect and the density of the magnetic core after molding and curing, thereby reducing losses.

[0026] (2) The present invention uses an addition-type curable silicone resin to bond ferrite magnetic powder. Compared with conventional silicone resins such as MQ silicone resin, it can be cured at a lower pressure and has a low preparation cost. Moreover, no additional organic solvents and lubricants are required, and the magnetic properties of the resulting magnetic core are better.

[0027] (3) The present invention can further reduce the core loss by further adjusting the ratio of low melting point glass powder to silicone resin adhesive. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0029] Example 1

[0030] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0031] (1) Preparation of insulation coating adhesive:

[0032] In parts by weight, 70 parts of vinyl silicone oil with a viscosity of 200 mPa·s and a vinyl content of 6.5%, 30 parts of hydrogen-containing silicone oil with a viscosity of 150 mPa·s and a hydrogen content of 1.2%, 0.01 parts of divinyltetramethyldisiloxane platinum complex catalyst, 0.1 parts of 1-ethynyl-1-cyclohexanol inhibitor and 20 parts of low-melting-point glass powder with an average particle size of 4 μm and a melting point of 400°C are mixed uniformly at room temperature to obtain an insulating coating adhesive.

[0033] (2) Preparation of low-loss inductor core:

[0034] Five parts of the obtained insulating coating adhesive were evenly mixed with 100 parts of manganese-zinc ferrite magnetic powder with an average particle size of 4 μm, firstly molded and cured for 10 minutes under nitrogen protection at 80°C and 400 MPa pressure, and then heated to 600°C under air conditions and sintered for 30 minutes to obtain a low-loss inductor core.

[0035] Example 2

[0036] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0037] (1) Preparation of insulation coating adhesive:

[0038] In parts by weight, 80 parts of vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 5.0%, 20 parts of hydrogen-containing silicone oil with a viscosity of 150 mPa·s and a hydrogen content of 1.2%, 0.01 parts of divinyltetramethyldisiloxane platinum complex catalyst, 0.1 parts of 1-ethynyl-1-cyclohexanol inhibitor and 20 parts of low-melting-point glass powder with an average particle size of 5 μm and a melting point of 350°C are mixed uniformly at room temperature to obtain an insulating coating adhesive.

[0039] (2) Preparation of low-loss inductor core:

[0040] 6 parts of the obtained insulating coating adhesive are evenly mixed with 100 parts of manganese-zinc ferrite magnetic powder with an average particle size of 5 μm, first molded and cured for 10 minutes under nitrogen protection at 80°C and 500 MPa pressure, and then heated to 600°C under air conditions and sintered for 30 minutes to obtain a low-loss inductor core.

[0041] Example 3

[0042] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0043] (1) Preparation of insulation coating adhesive:

[0044] In parts by weight, 60 parts of vinyl silicone oil with a viscosity of 200 mPa·s and a vinyl content of 6.5%, 40 parts of hydrogen-containing silicone oil with a viscosity of 1000 mPa·s and a hydrogen content of 0.8%, 0.01 parts of divinyltetramethyldisiloxane platinum complex catalyst, 0.1 parts of 1-ethynyl-1-cyclohexanol inhibitor and 20 parts of low-melting-point glass powder with an average particle size of 3 μm and a melting point of 450°C are mixed uniformly at room temperature to obtain an insulating coating adhesive.

[0045] (2) Preparation of low-loss inductor core:

[0046] 4 parts of the obtained insulating coating adhesive are evenly mixed with 100 parts of manganese-zinc ferrite magnetic powder with an average particle size of 3 μm, firstly molded and cured for 10 minutes under nitrogen protection at 80°C and 300 MPa pressure, and then heated to 700°C under air conditions and sintered for 30 minutes to obtain a low-loss inductor core.

[0047] Example 4

[0048] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0049] (1) Preparation of insulation coating adhesive:

[0050] In parts by weight, 70 parts of vinyl silicone oil with a viscosity of 200 mPa·s and a vinyl content of 6.5%, 30 parts of hydrogen-containing silicone oil with a viscosity of 150 mPa·s and a hydrogen content of 1.2%, 0.01 parts of divinyltetramethyldisiloxane platinum complex catalyst, 0.1 parts of 1-ethynyl-1-cyclohexanol inhibitor and 20 parts of low-melting-point glass powder with an average particle size of 4 μm and a melting point of 400°C are mixed uniformly at room temperature to obtain an insulating coating adhesive.

[0051] (2) Preparation of low-loss inductor core:

[0052] Five parts of the obtained insulating coating adhesive were evenly mixed with 100 parts of nickel-zinc ferrite powder with an average particle size of 4 μm, firstly molded and cured for 15 minutes under nitrogen protection at 80°C and 400 MPa pressure, and then heated to 600°C and sintered for 45 minutes under air conditions to obtain a low-loss inductor core.

[0053] Example 5

[0054] A method for preparing a low-loss inductor magnetic core. Compared with Example 1, the amount of low-melting-point glass powder added is increased to 30 parts, and the rest is the same.

[0055] Example 6

[0056] A method for preparing a low-loss inductor magnetic core. Compared with Example 1, the amount of low-melting-point glass powder added is increased to 40 parts, and the rest is the same.

[0057] Example 7

[0058] A method for preparing a low-loss inductor magnetic core. Compared with Example 1, the amount of low-melting-point glass powder added is increased to 50 parts, and the rest is the same.

[0059] Example 8

[0060] A method for preparing a low-loss inductor magnetic core. Compared with Example 1, the amount of low-melting-point glass powder added is reduced to 10 parts, and the rest is the same.

[0061] Example 9

[0062] A method for preparing a low-loss inductor magnetic core. Compared with Example 1, the amount of low-melting-point glass powder added is reduced to 5 parts, and the rest is the same.

[0063] Comparative Example 1

[0064] A method for preparing a low-loss inductor magnetic core. Compared with Example 1, the amount of low-melting-point glass powder added is reduced to 0 parts, and the rest is the same.

[0065] Comparative Example 2

[0066] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0067] (1) Preparation of insulation coating adhesive:

[0068] By weight, 100 parts of bisphenol A epoxy resin adhesive and 20 parts of low-melting-point glass powder with an average particle size of 4 μm and a melting point of 400° C. are uniformly mixed at room temperature to obtain an insulating coating adhesive.

[0069] (2) The preparation of the low-loss inductor core is the same as that in Example 1.

[0070] Comparative Example 3

[0071] A method for preparing a low-loss inductor magnetic core comprises the following preparation steps:

[0072] (1) Preparation of insulation coating adhesive:

[0073] By weight, 200 parts of MQ silicone resin toluene solution with a solid content of 50% and 20 parts of low-melting-point glass powder with an average particle size of 4 μm and a melting point of 400° C. are mixed uniformly at room temperature to obtain an insulating coating adhesive.

[0074] (2) The preparation of the low-loss inductor core is the same as that in Example 1.

[0075] The effective magnetic permeability (f=500kHz) and total loss (f=100kHz, Bm=50mT) of the inductor cores obtained in the above embodiments and comparative examples were tested, and the results are shown in Table 1 below.

[0076] Table 1

[0077] Test sample / performance Effective magnetic permeability <![CDATA[Total loss, mW / cm 3 > Example 1 76 256.2 Example 2 72 224.5 Example 3 85 278.9 Example 4 81 270.3 Example 5 82 275.6 Example 6 90 291.0 Example 7 122 430.2 Example 8 77 259.5 Example 9 75 286.4 Comparative Example 1 71 335.8 Comparative Example 2 78 365.7 Comparative Example 3 87 350.6

[0078] From the comparison results of Example 1 with Examples 5 to 9 and Comparative Example 1 in Table 1, it can be seen that with the increase of the content of low-melting glass powder in the insulating coating adhesive, the magnetic permeability of the obtained magnetic core shows an increasing trend, and the total loss shows a trend of first decreasing and then increasing. Although Comparative Example 1 without adding low-melting glass powder can achieve a good insulating coating effect and reduce eddy current loss, the air gap generated by high-temperature sintering cannot be effectively filled and the density of the magnetic core is reduced, resulting in a significant increase in hysteresis loss, and ultimately leading to an increase in total loss. Due to the addition of too much low-melting glass, Example 7 reduces the bonding and curing performance of the insulating coating adhesive, resulting in a reduction in the insulating coating effect and a reduction in the density of the magnetic core after molding and curing, and ultimately leading to a significant increase in total loss. When the addition amount of low-melting glass powder is 5% to 40% of the total mass of vinyl silicone oil and hydrogen-containing silicone oil, good comprehensive magnetic properties can be achieved. From the comparison results of Example 1 and Comparative Example 2, it can be seen that the combination of the silicone adhesive of the present invention and the low-melting glass powder can significantly reduce the core loss compared with the combination of conventional epoxy resin and low-melting glass powder. The reason is that the porous SiO2 generated by the organic silicon adhesive of the present invention during the later high-temperature sintering process can be used as a filling carrier for low-melting-point glass, which can significantly improve the insulation coating effect and the density of the magnetic core after molding and curing, thereby reducing eddy current loss and hysteresis loss. It can be seen from the comparison results of Example 1 and Comparative Example 3 that the use of the organic silicon adhesive of the present invention can further improve the insulation coating effect compared with the existing MQ silicone resin adhesive, thereby reducing eddy current loss.

[0079] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a low-loss inductor core, characterized in that: The method comprises the following preparation steps: (1) Preparation of insulation coating adhesive: The vinyl silicone oil, hydrogen-containing silicone oil, platinum complex catalyst, inhibitor and low-melting-point glass powder are uniformly mixed at room temperature to obtain an insulating coating adhesive; (2) Preparation of low-loss inductor core: The obtained insulating coating adhesive is mixed evenly with ferrite magnetic powder, firstly molded and cured at a temperature of 60-100°C and a pressure of 200-500MPa, and then heated to 500-800°C for sintering to obtain a low-loss inductor magnetic core.

2. The method for preparing a low-loss inductor magnetic core according to claim 1, characterized in that: The vinyl silicone oil in step (1) has a viscosity of 100 to 2000 mPa·s and a vinyl content of 1% to 10%; the hydrogen-containing silicone oil has a viscosity of 100 to 2000 mPa·s and a hydrogen content of 0.2% to 1.5%.

3. The method for preparing a low-loss inductor magnetic core according to claim 2, characterized in that: The mass ratio of the vinyl silicone oil to the hydrogen-containing silicone oil is 1:0.1-0.

6.

4. The method for preparing a low-loss inductor magnetic core according to claim 1, characterized in that: The amount of the platinum complex catalyst added in step (1) is 0.005% to 0.02% of the total mass of the vinyl silicone oil and the hydrogen-containing silicone oil; the inhibitor adopts an acetylene alcohol inhibitor, and the amount of the acetylene alcohol inhibitor added is 0.05% to 0.2% of the total mass of the vinyl silicone oil and the hydrogen-containing silicone oil.

5. The method for preparing a low-loss inductor magnetic core according to claim 1, characterized in that: The low-melting-point glass powder in step (1) has a particle size of 1 to 10 μm and a melting point of 300 to 600° C.

6. The method for preparing a low-loss inductor magnetic core according to claim 5, characterized in that: The added amount of the low melting point glass powder is 5% to 40% of the total mass of the vinyl silicone oil and the hydrogen-containing silicone oil.

7. The method for preparing a low-loss inductor magnetic core according to claim 1, characterized in that: The ferrite powder in step (2) is manganese-zinc ferrite powder or nickel-zinc ferrite powder with a particle size of 1 to 10 μm.

8. The method for preparing a low-loss inductor magnetic core according to claim 1, characterized in that: The mass ratio of the insulating coating adhesive to the ferrite magnetic powder in step (2) is 1:10-100.

9. The method for preparing a low-loss inductor magnetic core according to claim 1, characterized in that: The sintering treatment in step (2) is carried out under air conditions, and the sintering treatment time is 15 to 60 minutes.

10. A low-loss inductor core, characterized in that: It is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-magnetic-induction low-loss amorphous / nanocrystalline magnetic powder core based on core-shell functional element of magnetic conductive insulating shell and preparation method and application of high-magnetic-induction low-loss amorphous / nanocrystalline magnetic powder core

    CN116598117A

  • High-temperature insulation composite, insulated conductor and magnetic element

    CN101857724A

  • Powder for powder magnetic core, powder magnetic core, and methods for producing those products

    CN102132361A

  • Nano-magnetic silicon rubber as well as preparation method and application thereof

    CN102690521A

  • Preparation method for inorganic-organic composite adhesive-coated soft magnetic composite

    CN104070161A